1983
DOI: 10.1001/archderm.119.8.636
|View full text |Cite
|
Sign up to set email alerts
|

Association of chronic urticaria and angioedema with thyroid autoimmunity

Abstract: Seventeen patients, constituting 12.1% of 140 consecutively seen cases of chronic urticaria, demonstrated thyroid autoimmunity with thyroid microsomal antibodies (TMAs) in serum titers greater than or equal to 1:1,600. Eight of these 17 patients had goiter or thyroid dysfunction. In a control group of 477 consecutively seen patients, only 27 (5.6%) had similar TMA titers. Routine and special immunologic test results in this group of 17 patients did not differ from those found in other patients with chronic urt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
4
19

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 0 publications
5
100
4
19
Order By: Relevance
“…Female predilection was more prominent in chronic urticaria with high anti TPO antibody which was consistent with previous studies. [2][3][4][5][6][7] Severe urticaria was seen in patients with high anti TPO antibody in our study unlike most of the previous studies. 7,16,17 ASST positive patients also had high urticaria activity in our study, in concordance with other reports but unlike other studies where no correlation was found between the severity of urticaria and ASST positivity.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Female predilection was more prominent in chronic urticaria with high anti TPO antibody which was consistent with previous studies. [2][3][4][5][6][7] Severe urticaria was seen in patients with high anti TPO antibody in our study unlike most of the previous studies. 7,16,17 ASST positive patients also had high urticaria activity in our study, in concordance with other reports but unlike other studies where no correlation was found between the severity of urticaria and ASST positivity.…”
Section: Discussionmentioning
confidence: 54%
“…[5][6][7][8][9][10] Thyroid function was normal in the majority of patients with high anti-TPO antibody in our study. There was no statistically significant higher prevalence of anti TPO antibody in the ASST positive patients which also differ from other studies.…”
Section: Discussionmentioning
confidence: 89%
“…Leznoff et al 3 first suggested an autoimmune basis for chronic idiopathic urticaria (CIU) in 1983 after noting that there was an association between thyroid disease and CIU. This concept has been confirmed in several subsequent reports 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…The response rate to prednisone and azathioprine therapy is 80%, and nonresponders may be considered for a trial of cyclosporine, tacrolimus, or mycophenolate mofetil 2 . While the association between autoimmune urticaria and other autoimmune disorders such as thyroid disease is well known 3 , there has been no reported case of autoimmune urticaria concomitant with autoimmune hepatitis. We report a case of autoimmune urticaria concurrent with autoimmune hepatitis, which was successfully treated with cyclosporine.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Leznoff et al, the frequency of thyroid autoimmune disorders was investigated and a prevalence of 12.1% was reported (19). …”
Section: Anti-tpo Levels In Patientsmentioning
confidence: 99%